Limites e possibilidades ao desenvolvimento de um arranjo produtivo local de base florestal na serra do sudeste, Rio Grande do Sul, Brasil: governança local para tomada de decisões - Uberti, Gustavo Martins (2017)
The objective of this study is to evaluate the limits and the possibility of developing a Local Productive Arrangement (APL) of the Forest Base of the Serra do Sudeste, Rio Grande do Sul, in order to facilitate decision making by public-private entities. In order to encompass the counties in groups based on social and economic indicators that could provide greater subsidies for decision-making, were used two multivariate techniques the Hierarchical Clustering Analysis (HCA) and Primary Components Analysis (PCA). To classify the specificity of a sector were used three industrial agglomeration indicators: Location Quotient (LQ); Economic classes employment rate relative to the employment rate in the State (P); And the minimum quantity of establishments (E). Through these industrial agglomeration indicators, the agglomerate counties were classified according to their typology. The LPA analysis resulted in four groups: "Southern Waterfall", "Weak economic and social situation", "Industrial Conglomerate", and "Canguçu". The group "Industrial Conglomerate" was categorized in the typology called Sectorial / Regional Core of Development. Already the group "Canguçu" and "Weak economic and social situation" were categorized as Vector of Local Development, and the last group "Cachoeira do Sul" did not have enough parameters to be categorized according to the proposed methodology. The industrial agglomerate is indeed classified through the agglomeration indicators. Thus, it was possible to conclude that there is the possibility of developing a Local Productive Arrangement based on the Forest in the region of the Serra do Sudeste limited by Cachoeira do Sul, Pantano Grande, Dom Feliciano, Amaral Ferrador counties, highlighting the counties of Encruzilhada do Sul, Piratini, and Canguçu , Due to the salience in other counties by the number of companies and jobs. The main fact is an economic situation for the forestry sector that has developed in the region of the Southeast. At first, it is necessary to seek coordinating mechanisms among companies capable of developing main items, suggesting that a local governance has to be created.